The Effectiveness of Diabetic Self-Management Education (DSME) on Dietary Habit, Obesity, and Physical Activity Among Patients with DM Type II - Agow, Liana Lidia; Mendrofa, Fery Agusman Motuho; Sonhaji, Sonhaji (JURNAL INFO KESEHATAN, 2024)
Diabetes mellitus and metabolic disorders are the priority programs in Indonesia. There is one program to reduce the fatality impact of diabetes which is diabetic self-management education (DSME). This study aimed to examine the effectiveness of Diabetes Self-Management Education (DSME) on dietary habits, physical activity, and obesity.  This study is a quasi-experimental approach with one group pre-test post-test design. The sample in this study was 75 people with DM type II. The intervention for all samples was done for 4 sessions. Each session lasted 60 to 120 minutes/day with a maximum of 10 patients. The findings revealed that dietary habits were good from 56.0% to 69.3%, physical activity was good from 54.7% to 76.0%, and obesity decreased from 69.3% to 57.35, respectively for pre and post-test. The paired t-test result revealed that DSME correlates with dietary habits, physical activity, and obesity (obesity, physical activity, and dietary habit with p-values 0.024; 0.007; and 0.02, respectively). In conclusion, DSME has significantly influenced dietary habits, physical activity, and obesity. Education is crucial in promoting physical activity among individuals with diabetes. By enhancing self-efficacy, providing education on self-care behaviors, and emphasizing the importance of regular physical activity, these programs contribute to improving metabolic control, quality of life, and overall health outcomes in diabetic patients.